2021
DOI: 10.3390/polym13213703
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Hemocompatible pH-Responsive Hydrogel for Skin Wound Healing Application: In Vitro Drug Release

Abstract: The treatment of successive skin wounds necessitates meticulous medical procedures. In the care and treatment of skin wounds, hydrogels produced from natural polymers with controlled drug release play a crucial role. Arabinoxylan is a well-known and widely available biological macromolecule. We produced various formulations of blended composite hydrogels (BCHs) from arabinoxylan (ARX), carrageenan (CG), and reduced graphene oxide (rGO) using and cross-linked them with an optimal amount of tetraethyl orthosilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…For in vitro degradation assays, lyophilized Tsg-THA&Fe10, Tsg-THA&Fe20, Tsg-THA&Fe30, Tsg-THA&Fe40 and Tsg-THA&Fe50 hydrogel blocks of the same weight (0.5 g) were placed in 5 mL of PBS (pH 7.4, 37 °C), respectively, and the mixture was shaken uniformly at a rate of 100 r min −1 [ 41 ]. At scheduled time-points (4, 8, and 12 days), the hydrogel samples were collected, washed with deionized water, freeze-dried, and weighed.…”
Section: Methodsmentioning
confidence: 99%
“…For in vitro degradation assays, lyophilized Tsg-THA&Fe10, Tsg-THA&Fe20, Tsg-THA&Fe30, Tsg-THA&Fe40 and Tsg-THA&Fe50 hydrogel blocks of the same weight (0.5 g) were placed in 5 mL of PBS (pH 7.4, 37 °C), respectively, and the mixture was shaken uniformly at a rate of 100 r min −1 [ 41 ]. At scheduled time-points (4, 8, and 12 days), the hydrogel samples were collected, washed with deionized water, freeze-dried, and weighed.…”
Section: Methodsmentioning
confidence: 99%
“…This surface is rougher than typical, which helps to increase the surface area. By boosting ion transport and polymer chain mobility, it will improve the self-healing ability of hydrogels ( Khan et al, 2021d ; Zhao et al, 2022 ). It was also observed that increasing TEOS amount caused GO to cause more GO clustering at 300 µm as presented with red arrows.…”
Section: Resultsmentioning
confidence: 99%
“…If the crosslinking points are established by weak physical interactions, the water excess can determine the network disintegration up to complete dissolution. The amount of free and bound water can be determined by using different techniques and methods, such as: nuclear magnetic resonance, differential scanning calorimetry, X-ray powder diffraction, dielectric relaxation spectroscopy, quasi-elastic neutron scattering, infrared spectroscopy [93,94], diffusion or adsorption [40,41,59,62,63,95,96]. The main factors influencing the swelling process are: the crosslinking density, hydrophilicity of polymer chains, and characteristics of surrounding medium, such as pH or ionic strength and temperature.…”
Section: Swellingmentioning
confidence: 99%